Echocardiographic pressure-strain loop-derived stroke work of the right ventricle: validation against the gold standard - Richter, Manuel J.; Douschan, Philipp; Fortuni, Federico; Gall, Henning; Ghofrani, Hossein A.; Keranov, Stanislav; Kremer, Nils; Kriechbaum, Steffen D.; Rako, Zvonimir A.; Rieth, Andreas J.; da Rocha, Bruno Brito; Seeger, Werner; et al. (My University, 2023)
Aims: Commercially available integrated software for echocardiographic measurement of stroke work (SW) is increasingly used for the right ventricle, despite a lack of validation. We sought to assess the validity of this method [echo-based myocardial work (MW) module] vs. gold-standard invasive right ventricular (RV) pressure–volume (PV) loops. Methods and results: From the prospectively recruiting EXERTION study (NCT04663217), we included 42 patients [34 patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH) and 8 patients with absence of cardiopulmonary disease] with RV echocardiography and invasive PV catheterization. Echocardiographic SW was assessed as RV global work index (RVGWI) generated via the integrated pressure–strain MW software. Invasive SW was calculated as the area bounded by the PV loop. An additional parameter derived from the MW module, RV global wasted work (RVGWW), was correlated with PV loop measures. RVGWI significantly correlated with invasive PV loop-derived RV SW in the overall cohort [rho = 0.546 (P < 0.001)] and the PAH/CTEPH subgroup [rho = 0.568 (P < 0.001)]. Overall, RVGWW correlated with invasive measures of arterial elastance (Ea), the ratio of end-systolic elastance (Ees)/Ea, and end-diastolic elastance (Eed) significantly. Conclusions: Integrated echo measurement of pressure–strain loop-derived SW correlates with PV loop-based assessment of RV SW. Wasted work correlates with invasive measures of load-independent RV function. Given the methodological and anatomical challenges of RV work assessment, evolution of this approach by incorporating more elaborated echo analysis data and an RV reference curve might improve its reliability to mirror invasively assessed RV SW.
Keywords: ddc:610